Improved Y-STR typing for disaster victim identification, missing persons investigations, and historical human skeletal remains - Ambers, Angie; Votrubova, Jitka; Vanek, Daniel; Sajantila, Antti; Budowle, Bruce (International journal of legal medicine, 2018)
Bones are a valuable source of DNA in forensic, anthropological, and archaeological investigations. There are a number of scenarios in which the only samples available for testing are highly degraded and/or skeletonized. Often it is necessary to perform more than one type of marker analysis on such samples in order to compile sufficient data for identification. Lineage markers, such as Y-STRs and mitochondrial DNA (mtDNA), represent important systems to complement autosomal DNA markers and anthropological metadata in making associations between unidentified remains and living relatives or for characterization of the remains for historical and archaeological studies. In this comparative study, Y-STR typing with both Yfiler™ and Yfiler™ Plus (Thermo Fisher Scientific, Waltham, MA, USA) was performed on a variety of human skeletal remains, including samples from the American Civil War (1861-1865), the late nineteenth century gold rush era in Deadwood, SD, USA (1874-1877), the Seven Years' War (1756-1763), a seventeenth-century archaeological site in Raspenava, Bohemia (Czech Republic), and World War II (1939-1945). The skeletal remains used for this study were recovered from a wide range of environmental conditions and were extracted using several common methods. Regardless of the DNA extraction method used and the age/condition of the remains, 22 out of 24 bone samples yielded a greater number of alleles using the Yfiler™ Plus kit compared to the Yfiler™ kit using the same quantity of input DNA. There was no discernable correlation with the degradation index values for these samples. Overall, the efficacy of the Yfiler™ Plus assay was demonstrated on degraded DNA from skeletal remains. Yfiler™ Plus increases the discriminatory power over the previous generation multiplex due to the larger set of Y-STR markers available for analysis and buffer modifications with the newer version kit. Increased haplotype resolution is provided to infer or refute putative genetic relationships.
Keywords: Historical remains; Chromosomes, Human, Y; nekrotická degradace DNA; lidský chromozom Y; polymerázová řetězová reakce; Polymerase Chain Reaction; DNA Fingerprinting; Body Remains; oběti katastrofy; kosti a kostní tkáň; lidé; Y-STR typing; Yfiler™ Plus; Degraded DNA; DNA fingerprinting; Lineage testing; Disaster Victims; DNA Degradation, Necrotic; Skeletal remains; Microsatellite Repeats; alely; Alleles; Rapidly mutating Y-STRs; Bone and Bones; mikrosatelitní repetice; tělesné pozůstatky; Humans